Agile auditing : fundamentals and applications - Catlin, Raven; Watkins, Ceciliana (John Wiley & Sons, Inc., 2021)
"Audits are laden with performance problems that cause delays in completing audit work and delivering valuable information to audit clients and stakeholders. Agile is a topic of discussion in many disciplines especially for software development and is just starting to find its way to audit. Agile project management has been used for nearly two decades to solve common problems in projects. The audit profession is eager to find solutions to fix problems in audit project management. Agile auditing is a solution to many of the common problems. Very few auditors understand agile beyond the agile mindset. This book will help auditors conduct audits better, faster, and more effectively. It teaches the "how to" implement agile auditing. The authors leverage hands-on experience with three audit departments and dialogue with a dozen other audit shops that applied agile auditing to provide in-depth insight on how to effectively implement agile auditing. A discussion of how internal audit shops in government agencies can become more agile in their work is also included."- Resumé vydavatele
Keywords: audit; projektový management; auditing; project management; elektronické knihy; monografie; electronic books; monographs